1964
DOI: 10.1128/jb.88.5.1205-1210.1964
|View full text |Cite
|
Sign up to set email alerts
|

METABOLIC ACTIVITY INCOXIELLA BURNETII

Abstract: Purified suspensions of Coxiella burnetii were shown to utilize a-ketoglutarate, succinate, fumarate, malate, oxaloacetate, pyruvate, glutamate, and serine. The addition of nicotinamide adenine dinucleo-tide+ was necessary to elicit the maximal rate of oxygen uptake with L-glutamate as substrate, but was unnecessary when other substrates were employed. It was concluded that the Krebs cycle of intermediary carbohydrate metabolism probably operates within C. burnetii, and that pyruvate is the chief energy source. Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0
1

Year Published

1967
1967
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 19 publications
0
15
0
1
Order By: Relevance
“…Previous studies have shown that tricarboxylic acid cycle intermediates are preferentially metabolized by purified C. burnetii (13); however, these studies were carried out in a reaction buffer of approximately pH 7.25, a value much greater than the optimum pH at which this organism actively transports and metabolizes these substrates (5). In a similar study (15), glucose was reported not to be utilized by intact C. burnetii.…”
Section: Resultsmentioning
confidence: 92%
“…Previous studies have shown that tricarboxylic acid cycle intermediates are preferentially metabolized by purified C. burnetii (13); however, these studies were carried out in a reaction buffer of approximately pH 7.25, a value much greater than the optimum pH at which this organism actively transports and metabolizes these substrates (5). In a similar study (15), glucose was reported not to be utilized by intact C. burnetii.…”
Section: Resultsmentioning
confidence: 92%
“…Although metabolic activity of C. burneti was demonstrated only with considerable difficulty when whole cells were used (14), experiments with cell extracts have been quite productive. Of the 16 enzymatic activities investigated in this study, the following 10 were demonstrated in C. burneti: citrate synthase, MDH, and NAD-dependent GDH (17); NADP-dependent IDH and glucose-6-phosphate dehydrogenase (4); 6-phosphogluconate dehydrogenase (10); phosphoglucose isomerase, fructoaldolase, glyceraldehyde-3-phosphate dehydrogenase, and pyruvate kinase (11).…”
Section: Discussionmentioning
confidence: 99%
“…These experiments and those we present indicate that there is a VOL. 14,1976 on July 16, 2020 by guest http://iai.asm.org/ Downloaded from profound difference between typhus and Q fever rickettsiae in their physiological properties. Although there is little doubt that both groups of organisms possess a functioning tricarboxylic acid cycle, only the latter appear to be capable of glucose catabolism.…”
Section: Discussionmentioning
confidence: 99%
“…The study of bacteria with an obligate intracellular lifestyle presents a particular challenge and it can be difficult to determine and reproduce the environmental conditions required for metabolic activity. For example, initial work investigating the metabolism of Coxiella burnetii used neutral pH buffers and concluded that there was negligible activity (Ormsbee & Peacock, 1964). When acidic buffers were used, metabolism was markedly enhanced (Hackstadt & Williams, 1981).…”
Section: Reasons For 'Unculturability'mentioning
confidence: 99%